Development of Sai Krok E-san Kai (Chicken Fermented Sausages) with Riceberry Rice - Onnompun, Ekapon; Pasurakul, Pawitra; Prapluettrakul, Bencharat; Kulawit, Nuchanart; Pornsuksawat, Pornyupan; Wirunthanakrit, Weerapong; Vittayaporn, Varaporn (Journal of Food Health and Bioenvironmental Science, 2023)
This research aims to (1) study the ratios of sticky rice to Riceberry rice in Sai Krok E-san Kai with Riceberry rice, at 70:30, 50:50 and 0:100 (2) compare the nutritional value between control Sai Krok E-san Kai and Sai Krok E-san Kai with Riceberry rice and (3) carry out consumers’ acceptance test of Sai Krok E-san Kai with Riceberry rice. The study showed that the most accepted ratio of sticky rice to Riceberry rice is 50:50, with overall liking score of 7.48±1.14 (moderately like to like very much). From the comparison of nutritional value in control Sai Krok E-san Kai and Sai Krok E-san Kai with Riceberry rice, it was found that the control sample had 181.29 kcal of energy, 8.29 g fat, 13.12 g carbohydrate, 2.58 g dietary fiber, 0.45 mg iron and 0.69 mg zinc. On the other hand, Sai Krok E-san Kai with Riceberry rice had 163.65 kcal of energy, 7.49 g fat, 10.34 g carbohydrate, 4.86 g dietary fiber, 0.97 mg iron and 0.75 mg zinc. Moreover, the consumer acceptance test of Sai Krok E-san Kai with Riceberry rice showed that, out of 100 panelists, 89% accepted the product and 75% decided that they would purchase the product.